Live pig markets are hotspots for spread of African swine fever virus in Nigeria. Issue 5 (5th March 2022) - Adedeji, Adeyinka J.; Atai, Rebecca B.; Gyang, Helen E.; Gambo, Panzam; Habib, Maimuna A.; Weka, Rebecca; Muwanika, Vincent B.; Masembe, Charles; Luka, Pam D.
Abstract: Livestock trading through live animal markets are potential pathways for the introduction and spread of economically important pathogens like the African swine fever virus (ASFV) to new areas in several countries. Due to the high demand for live pigs in Nigeria both for restocking and slaughter, live pigs are sold at designated live pig markets (LPM) in the country. This involves movement of pigs over long distances. Despite, reports of ASF outbreaks following restocking of pigs bought from LPMs, there is paucity of information on the role of LPMs in the epidemiology of ASF. In this study, data and pig samples (whole blood, sera, tissue) were collected from 4 selected LPMs in Nigeria (Dawaki, Katsit, Numan and Pandam) between 2019 and 2020. Samples were analysed by polymerase chain reaction (PCR) and enzyme‐linked immunosorbent assay (ELISA). Four genes of ASFV positive samples were characterized to identify the circulating genotypes. Results revealed trade activities involving transportation of pigs from these selected markets to 42 major cities and towns in thirteen (13) States of Nigeria. PCR results revealed an overall ASF prevalence of 10.77% (66/613). ASFV was confirmed by PCR in all the selected LPMs with a prevalence rate of 3.13%–23.81%. The phylogeny revealed genotype I and serogroup 4 based on the p72 protein that encodes the B646L gene and the EP402R gene encoding the CD2V. While sequence analysis of CVR of B602L gene revealed 8 tetrameric repeats variants, six of which have never been reported in Nigeria. Analysis of sera samples recorded a seroprevalence of 6.9% (16/217) within the study period. Findings from this study show that LPM are hotspots and channels for transmission and continuous spread of ASFV in Nigeria. Therefore, for ASF to be controlled in Nigeria, disease surveillance and regulation at LPMs are critical.